Molecular and virulence differences of Klebsiella pneumoniae isolated from blood - Xu, Zhaoxia; Xiong, Yuxuan; Duan, Xueguang; Han, Jing; Xiang, Xing; Han, Ran; Zhang, Shengwei (Frontiers in Microbiology, 2025)
BackgroundBloodstream infections (BSIs) accompanied by sepsis with Klebsiella pneumoniae (K. pneumoniae) represents a public health threat being potentially life-threatening. There have been an increasing number of reports on K. pneumoniae isolates in China. We conducted a case-based genomic and experimental study. We studied the diversity of K. pneumoniae isolated from blood causing sepsis to reveal differences between patients.MethodsThe isolates from six patients infected with K. pneumoniae from January 2022 to April 2023 were analyzed by antimicrobial susceptibility testing and sequenced by whole genome sequencing (WGS). The data collected were used to investigate their serotype, molecular subtype, and virulence-associated and antimicrobial resistance (AMR) genes contents as well as the presence of plasmids.ResultsWGS data revealed that six isolates clustered in 5 different genetic types, 3 of which identified as carbapenem-resistant K. pneumoniae (CRKp) isolates, 2 as hypervirulent K. pneumoniae (hvKp) isolates. Among them, the serotype of Kpn3 is ST950, which is a relatively new serotype strain in China. CRKp isolates were resistant to almost all antibiotics and carries multiple plasmids with different resistance genes. They all contained the KPC-2 gene, but their blaKPC-2-harbored plasmids were different. 2 hvKp isolates belonged to 2 different sequence types, ST23 and ST65, respectively. HvKp with a hypermucoviscosity phenotype had a higher mortality rate in mice. However, they had less plasmid and antimicrobial resistance genes than CRKp, and were susceptible to all tested antimicrobial drugs.ConclusionThis study provided important insights into the diversity between K. pneumoniae strains isolated from blood in the same hospital. K. pneumoniae isolated from different patients has diversity of drug resistance genes, virulence genes and plasmids, which may affect the outcome of patients. Therefore, accurate treatment of patients according to the molecular characteristics and drug resistance phenotype of the isolates will achieve better efficacy.